Abnormal cortical lysosomal β-hexosaminidase and β-galactosidase activity at post-synaptic sites during Alzheimer's disease progression. (January 2015) - Magini, Alessandro; Polchi, Alice; Tozzi, Alessandro; Tancini, Brunella; Tantucci, Michela; Urbanelli, Lorena; Borsello, Tiziana; Calabresi, Paolo; Emiliani, Carla
Highlights: Glycohydrolase Hex and Gal activities increase in the cortex of advanced AD mouse. Hex and Gal are specifically associated with post-synaptic lipid microdomains. Hex and Gal activities increase in the post-synapses of early and advanced AD mice. Abnormal post-synaptic enzyme activities represent a precocious event related to AD. Abstract: A critical role of endosomal–lysosomal system alteration in neurodegeneration is supported by several studies. Dysfunction of the lysosomal compartment is a common feature also in Alzheimer's disease. Altered expression of lysosomal glycohydrolases has been demonstrated not only in the brain and peripheral tissues of Alzheimer's disease patients, but also in presymptomatic subjects before degenerative phenomenon becomes evident. Moreover, the presence of glycohydrolases associated to the plasma membrane have been widely demonstrated and their alteration in pathological conditions has been documented. In particular, lipid microdomains-associated glycohydrolases can be functional to the maintenance of the proper glycosphingolipids pattern, especially at cell surface level, where they are crucial for the function of cell types such as neurons. In this study we investigated the localization of β-hexosaminidase and β-galactosidase glycohydrolases, both involved in step by step degradation of the GM1 to GM3 gangliosides, in lipid microdomains from the cortex of both an early and advanced TgCRND8 mouse model of Alzheimer's disease. Throughout immunoprecipitation experiments of purified cortical lipid microdomains, we demonstrated for the first time that β-hexosaminidase and β-galactosidase are associated with post-synaptic vesicles and that their activities are increased at both the early and the advanced stage of Alzheimer's disease. The early increase of lipid microdomain-associated β-hexosaminidase and β-galactosidase activities could have relevant implications for the pathophysiology of the disease since their possible pharmacological manipulation could shed light on new reliable targets and biological markers of Alzheimer's disease.